History education: interactive and collaborative learning through gamification (based on Malaysian curriculum) - Shari, Norhasimah; Zulkifle, Nurul Atiqah; Fernandez, Diane Christine; Mohamad Santosa, Muhamad Syahmi; Zaini, Nur Suhaina Izzati; Krishnamoorthy, Pasumitha; Yeow, Hui En; Jamaludin, Fazdlina (Academica Press Solutions, 2023)
The number of students passing History in secondary school has shown a downward trend recently. Among the factors contributing to the downward trend are that students think that History subject is difficult to learn as students require knowing many facts, and History is considered boring among school students. The younger generation is known to live with multiple devices, such as computers and mobile phones. However, using these devices in learning activities has not been actively adopted in the Malaysian school environment, and the system still uses a conventional method to deliver the syllabus. Using teaching aids such as interactive videos and gamification techniques helps teaching and learning activities become more interesting and effective through blended learning. The integration of gamification techniques in non-game settings, especially education, has rapidly increased to enhance learner motivation, engagement, performance and provide a better learning experience. The innovation in history education through gamification can be used in formal and informal education settings. History education through gamification techniques can contribute to a more flexible, innovative, and creative syllabus that can be used for face-to-face and online learning. Moreover, it is recommended that such education gamification be commercialized and included as a free source for all Malaysian students to ensure education reachability and accessibility. With this idea put forward, it is hoped that the policymakers and government may subsidies such applications to spark students' interest in learning History in a fun and interactive manner.